Complementary Feeding Methods, Feeding Problems, Food Neophobia, and Picky Eating among Polish Children - Agnieszka Białek-Dratwa; Oskar Kowalski (MDPI AG, 2023)
Proper nutrition during the first period of life is primarily related to meeting energy needs and providing essential nutrients that ensure the infant's normal physical and psychomotor development. Improper nutrition during this period, inadequate amounts of nutrients, inappropriate timing and manner of introduction of individual foods, can permanently alter metabolism and the course of physiological processes, increasing the risk of diseases such as obesity, allergic diseases, and cardiovascular diseases. This study aimed to verify how the method of complementary feeding influences the occurrence of food neophobia between 2 and 7 years of age, as well as to assess the different nutritional aspects resulting from the process of starting feeding other than breast milk and milk formula. In this study, 490 mothers and their children aged 2-7 years participated. The research tool was a questionnaire consisting of a child's dietary assessment and standardized questionnaires assessing food neophobia among children: Food Neophobia Scale for Children (FNSC) and the Montreal Children's Hospital-Pediatric Feeding (MCH-FS). In the study group of children, 238 (48.57%) had no Baby-Led Weaning Method (no BLW) method used during complementary feeding (CF), and 252 (51.42%) children used Baby-Led Weaning Method (BLW). According to the FNSC questionnaire, a high risk of food neophobia was found in 32.65% of the children studied and a medium risk in 39.80%. The medium risk of feeding problem occured in 11.63% of children, the high risk in 6.73% of children, and the highest risk in 6.94% (MCH-FS). No statistically significant differences were observed between the BLW and NoBLW groups. High risk of food neophobia occured in 1/3 of the children studied, but there was no relationship in the study group between the mode of CF (BLW/NoBLW) and the risk of food neophobia.